IMPLEMENTATION OF EVIDENCE-BASED CLINICAL-AND-MORPHOLOGICAL APPROPRIATE USE CRITERIA FOR CORONARY REVASCULARIZATION IN PATIENTS WITH ACUTE CORONARY SYNDROME IN RUSSIA - Yu. V. Popova; O. M. Posnenkova; A. R. Kiselev; V. I. Gridnev; P. Ya. Dovgalevsky (Кардиоваскулярная терапия и профилактика)
Aim. To study possibility of using the evidence-based clinical-andmorphological appropriate use criteria for percutaneous coronary interventions (PCIs) for expert evaluation of high-technology procedures implementation in patients with acute coronary syndrome (ACS) in Russia.Materials and methods. The appropriateness of performed PCI was assessed in patients with ACS, underwent coronary revascularization. The potential need in PCI was determined in ACS patients refused from coronary revascularization. Assessment was performed with the help of ACCF/SCAI/STS/AATS/AHA/ASNC/HFSA/SCCT 2012 Appropriate Use Criteria for Coronary Revascularization Focused Update (ACCF 2012). Data from 65,912 ACS patients, containing in Russian ACS Registry (2010–2011) were examined.Results. ACCF 2012 criteria allow to assess the clinical appropriateness of PCI in 79.2% of patients underwent coronary revascularization and to determine the potential need in PCI in 80.6% of patients, refrained from coronary revascularization. Among ACS patients underwent PCI (n=9147), intervention was appropriate in 68.9% of cases. Inappropriate PCI was revealed in 4.6% of cases. Among patients refrained from PCI (n=56765), coronary revascularization was potentially appropriate in 57.9% of cases.Conclusion. ACCF 2012 clinical-and-morphological criteria allow to judge on appropriateness of performed PCI and to evaluate the potential need in PCI among the most part of Russian ACS patients. In present study coronary revascularization was appropriate in the majority of ACS patients. It was shown possible to use the evidence-based clinical-andmorphological criteria for expert evaluation of high-technology procedures implementation in Russian ACS patients.